Pengaruh Kualitas Pelayanan dan Disiplin Kerja Terhadap Kinerja Pegawai: Studi Kasus Pada Pegawai Kantor Desa Baregbeg Kecamatan Lakbok - Intan Gatty Nugraha; Enas Enas; Ferey Herman (Universitas 45 Surabaya, 2024)
This research was motivated by the low work ethic and low quality of service provided by officers at the Baregbeg Village Office, Lakbok District, which was the driving force for this research. This can be seen from the many complaints from the public regarding various issues related to employee performance. Employees at the Baregbeg Village Office are able to operate optimally if a service is handled well. Employee performance is influenced by several factors, including service quality and work discipline. The purpose of this research is to be able to find out a problem formulation, namely whether or not service quality and work discipline influence employee performance. Service quality, which also considers how well the service is carried out, will determine the level of community satisfaction. Effective employee performance in the workplace is very dependent on work discipline. The following findings from this research use quantitative approach techniques and explanatory methods, with the following results: 1. Employee performance is significantly and partially influenced by service quality, this is indicated by the t test value of 4.259, 2. Employee performance is significantly and partially positively influenced by work discipline, with a t test value of 4.904, 3. Employee performance is influenced positively and significantly by service quality and work discipline as indicated by the F test result of 37.329.